Trade Disruption, Industrialisation, and the Setting Sun of British Colonial Rule in India - Roberto Bonfatti; Björn Brey (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Colonial trade encouraged the colonies to specialise in primary products. Did this prevent in-dustrialisation in the colonies? And did lack of industrialisation, in turn, help to keep the colonies under control? To answer these questions, we examine the impact of the temporary collapse in trade between Britain and India due to World War I, on industrialisation and anti-imperial feelings in India. Exploiting cross-district variation in exposure to the trade shock stemming from initial differences in industrial specialisation, we find that districts more exposed to the trade shock experienced substantially faster industrial growth in 1911-21, placing them on a higher level of industrialisation which has persisted up to today. Using the World War I trade shock as an instrument for industrialisation levels, we also find that more industrialised districts were more likely to express anti-imperial feelings in 1922, and to vote for the Indian National Congress in the landmark election of 1937. These results suggest that colonial trade may have played an important role in preventing colonial industrialisation, and in embedding foreign rule.
Keywords: F14; F54; O14; N65; 330; colonial trade; India; infant-industry argument; decolonisation